Different Shades of Listeria monocytogenes: Strain, Serotype, and Lineage-Based Variability in Virulence and Stress Tolerance Profiles - Muchaamba, Francis; Eshwar, Athmanya K.; Stevens, Marc J. A.; Stephan, Roger; Tasara, Taurai (Frontiers in Microbiology, 2022)
Listeria monocytogenes is a public health and food safety challenge due to its virulence and natural stress resistance phenotypes. Variable distribution of L. monocytogenes molecular subtypes with respect to food products and processing environments as well as among human and animal clinical listeriosis cases is observed. Sixty-two clinical and food-associated L. monocytogenes isolates were examined through phenome and genome analysis. Virulence assessed using a zebrafish infection model revealed serotype and genotype-specific differences in pathogenicity. Strains of genetic lineage I serotype 4b and MLST clonal complexes CC1, CC2, CC4, and CC6 grew and survived better and were more virulent than serotype 1/2a and 1/2c lineage II, CC8 and CC9 strains. Hemolysis, phospholipase activity, and lysozyme tolerance profiles were associated to the differences observed in virulence. Osmotic stress resistance evaluation revealed serotype 4b lineage I CC2 and CC4 strains as more osmotolerant whereas serotype 1/2c lineage II CC9 strains were more osmo-sensitive than others. Variable tolerance to the widely used quaternary ammonium compound benzalkonium chloride (BC) was observed. Some outbreak and sporadic clinical case associated strains demonstrated BC tolerance, which might have contributed to their survival and transition in the food processing environment facilitating food product contamination and ultimately outbreaks or sporadic listeriosis cases. Genome comparison uncovered various moderate differences in virulence and stress associated genes between the strains indicating that these differences in addition to gene expression regulation variations might largely be responsible for the observed virulence and stress sensitivity phenotypic differences. Overall, our study uncovered strain and genotype dependent variation in virulence and stress resilience among clinical and food-associated L. monocytogenes isolates with potential public health risk implications. The extensive genome and phenotypic data generated provides a basis for developing improved Listeria control strategies and policies.